Industrial Heritage. A Future for the Past from a European Perspective - Álvarez-Areces, Miguel Ángel; Comité Internacional para la Salvaguarda del Patrimonio Industrial, ticcih-España. (Instituto Carlos Arbeláez Camacho para el patrimonio arquitectónico y urbano, 2014)
an introduction to industrial heritage this paper addresses different meanings and relevant facts that make it anessential issue in heritage contexts, beginning with industrial archeology as an academic discipline.In the 1970s, valuing landscapes and territories and considering industrial heritage as a new heritage category stirredpublic awareness. Later on, inventories, conservation, preservation and redeveloping industrial heritage policies weredeveloped, valuing it at first as isolated objects and later on as ensembles. Today, the main issue is that communitiesneed to recognize the value of the industrial heritage ensembles and landscapes.At present, the World Heritage List includes more than 50 industrial heritage sites, and more efforts are being madeto include these objects in local development plans.